A Study on Employee Retention in a Construction Company - Chew, Siew Yee (2012)
Many construction companies experiences high attrition, which negatively impacts the construction industry. This study’s objective was to identify employees are leaving and propose retention initiatives. The research instrument used to obtain data was questionnaire. A total of 200 questionnaires were randomly distributed to employees from construction companies. Researcher has also conducted interview with the subject expert. However, only 100 respondents returned the completed questionnaires. Correlation analysis was used to test the inter correlation between the variables. Correlation result shows that these two variables of motivation and job satisfaction were correlated with employee retention in the organization. The Pearson correlation used to measure the significance of linear bivariate between the independent and dependent variables thereby achieving the objectives of this study. Linear regressions used to determine the relationship between independent and dependent variables, the direction of the relationship and strength of the relationship. Results indicate attrition is associated with compensation, work hours, staffing and improper selection/hiring of employees. These findings show that the related factors should be given attention to retain employees in the organisation.